Analysis of Psychometric Properties of Child and Adolescent Mindfulness Measure (CAMM) and Mindful Attention Awareness Scale for Adolescents (MAAS-A) - Setyoko, Rahmad (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This study aims to analyze the psychometric properties of the Child and Adolescent Mindfulness Measure (CAMM) and the Mindfulness Attention Awareness Scale – Adolescents (MAAS-A) which are popularly used to measure the level of mindfulness in adolescents. The method used is a quantitative research method using a comparative descriptive approach. The sample in this study was 44 students of Pasastrian Buddhis Kusalamitra Gunungkidul consisting of 18 male students and 26 female students. Data analysis used is the Cronbach's Alpha reliability test, Exploratory Factor Analysis with the KMO-MSA test, univariate analysis, and t-Test.The results showed that the CAMM reliability coefficient was 0.757, the KMO value was 0.731, the Anti Image Correlation on 10 CAMM items met the valid criteria (>0.5), and the measurement results showed an average score of 19.27 with a standard deviation of 5.70. The MAAS-A reliability coefficient was 0.820, the KMO score was 0.712, the Anti Image Correlation on 14 MAAS-A items met the valid criteria (>0.5), and the MAAS-A measurement results showed an average score of 51.88 with a standard deviation of 10.54. In terms of objectivity and sensitivity, CAMM is more suitable for the population of children and young adolescents, while MAAS-A is more relevant for adolescents who have entered the formal cognitive development stage.